Ultraviolet radiation-induced immunosuppression and its relevance for skin carcinogenesis. Issue 12 (14th November 2017) - Hart, Prue H.; Norval, Mary
Abstract : Major steps in the pathway leading to the increased risk of skin cancer by the immunosuppression induced by UVR exposure. Abstract : The realisation that UV radiation (UVR) exposure could induce a suppressed immune environment for the initiation of carcinogenesis in the skin was first described more than 40 years ago. Van der Leun and his colleagues contributed to this area in the 1980s and 90s by experiments in mice involving UV wavelength and dose-dependency in the formation of such tumours, in addition to illustrating both the local and systemic effect of the UVR on the immune system. Since these early days, many aspects of the complex pathways of UV-induced immunosuppression have been studied and are outlined in this review. Although most experimental work has involved mice, it is clear that UVR also causes reduced immune responses in humans. Evidence showing the importance of the immune system in determining the risk of human skin cancers is explained, and details of how UVR exposure can down-regulate immunity in the formation and progression of such tumours reviewed. With increasing knowledge of these links and the mechanisms of UVR-induced immunosuppression, novel approaches to enhance immunity to skin tumour antigens in humans are becoming apparent which, hopefully, will reduce the burden of UVR-induced skin cancers in the future.